2021
DOI: 10.11648/j.jmpt.20210701.11
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Post Annealing Rates on Porosity, Dispersion Energy and Associated Dielectric Energy Losses of TiO<sub>2</sub> Thin Films

Abstract: With scientific and technological advances, Titanium dioxide (TiO 2 ) has attracted great research interest in the field of Dye Sensitized Solar cells (DSSC) with an aim to improve its efficiency. In this study, transparent semiconducting titanium dioxide thin films were deposited on glass substrate coated with fluorine tin IV oxide (SnO 2 : F) film by sol gel technique. The films were then annealed in air up to 450°C at different annealing rates. Optical reflectance was measured using UV-Vis-NIR spectrophotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
0
0
1
Order By: Relevance
“…Authors [51] found higher values of porosity for TiO2 film anchored on FTO than the values we find of TiO2 on graphene due to the large surface area of graphene that offer a scaffold anchor of TiO2. Tiny gaps and voids at the FTO/TiO2 interface cause higher porosity due to the uneven microstructure of FTO glass.…”
Section: As a Function Of Photon Energycontrasting
confidence: 58%
“…Authors [51] found higher values of porosity for TiO2 film anchored on FTO than the values we find of TiO2 on graphene due to the large surface area of graphene that offer a scaffold anchor of TiO2. Tiny gaps and voids at the FTO/TiO2 interface cause higher porosity due to the uneven microstructure of FTO glass.…”
Section: As a Function Of Photon Energycontrasting
confidence: 58%